"Most [False Reports] Involve Teens": Officer Attitudes Toward Teenage Sexual Assault Complainants—A Qualitative Analysis. (January 2020) - O'Neal, Eryn Nicole; Hayes, Brittany E.
Scholars, advocates, and victims have repeatedly criticized the police treatment of sexual assault (SA) complainants. Apathetic attitudes and hostile behavior on the part of the police have likely resulted from socialization into a culture that condones the use of force and violence and blames SA victims for their victimization. Using data from in-depth semistructured interviews with 52 Los Angeles Police Department sex crimes detectives, we examine officer attitudes toward teenage complainants of SA. Notably, almost three fourths of the respondents ( n = 38; 73%) mentioned that teenagers lie about SA. Practical implications, theoretical advancements, and directions for future research are discussed.